The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1029/2020ja028625
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Ionospheric Response to the 14 December 2020 Total Solar Eclipse Using SUPIM‐INPE

Abstract: We present the first prediction of the ionospheric response to the 14 December 2020 solar eclipse using the SUPIM-INPE model. Simulations are made for all known ionosonde stations for which solar obscuration is significant. The found response is similar to that previously reported for other eclipses, but it also shows a modification of the equatorial fountain transport that will impact the low latitudes after the event. In addition to the large reduction of electron concentration along the totality path (~4.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 83 publications
(151 reference statements)
0
20
1
Order By: Relevance
“…For an in-depth discussion on the use of SAMI3 to predict ionospheric behavior during solar eclipses, see J. D. Huba and Drob (2017) and Senapati et al (2020). A more detailed modeling effort of the predicted TEC response to this TSE can be found in Martínez-Ledesma et al (2020).…”
Section: Observations Of the 2020 Total Solar Eclipsementioning
confidence: 99%
See 1 more Smart Citation
“…For an in-depth discussion on the use of SAMI3 to predict ionospheric behavior during solar eclipses, see J. D. Huba and Drob (2017) and Senapati et al (2020). A more detailed modeling effort of the predicted TEC response to this TSE can be found in Martínez-Ledesma et al (2020).…”
Section: Observations Of the 2020 Total Solar Eclipsementioning
confidence: 99%
“…A more detailed modeling effort of the predicted TEC response to this TSE can be found in Martínez‐Ledesma et al. (2020).…”
Section: Observations Of the 2020 Total Solar Eclipsementioning
confidence: 99%
“…At these altitudes, diffusion and transport plasma processes generally dominate the ionospheric behavior, making the ionospheric response to the eclipse highly dependent on different latitudinal effects (Le et al, 2009). In particular, multiple studies have demonstrated that the ionospheric response to eclipses at equatorial and low latitudes is dominated by the fountain effect and the Equatorial Ionization Anomaly (EIA; e.g., Martínez-Ledesma et al, 2020;Bravo et al, 2020;Jonah et al, 2020;Jose et al, 2020;Cheng et al, 1992;Le et al, 2009). Furthermore, the multiple coupling processes that interact in the magnetosphere-ionosphere-thermosphere system and the internal ionospheric processes provide large variability to the ionospheric state (Sarris, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the ionospheric response to the 14 December 2020, solar eclipse measured over South America is compared to the SUPIM-INPE model prediction made by Martínez-Ledesma et al (2020). Here, we evaluate the response along the South-American continent, covering a wide range of geomagnetic latitudes, from the Equator (e.g., Jicamarca) to mid-latitude sectors (e.g., Bahía Blanca).…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in foF2 and hmF2 is notorious at stations near the anomaly's crest (RA, FZ, CP); however, it is not very significant in the stations at the magnetic equator (SL). Moreover, similar ionospheric effects were seen in distant regions in the moon's shadow [16][17][18][19][20][51][52][53][54][55][56]. Differences between foF2 and TEC may be due to the fact that foF2 was the result of the original autoscaled records, and also that TEC was calculated from a spatial average.…”
Section: Ionospheric Behaviormentioning
confidence: 85%